The study of 7ps marketing mix on purchase intention in the home renovation service industry using PLS-SEM approach - Kartika, Kristi; Aprianingsih, Atik (Manajemen dan Bisnis, 2026)
The increasing demand for home renovation service, coupled with the growing number of households in Indonesia, has also increased competition in this sector. Businesses whose revenue depends on new projects require the right marketing strategy to increase customer acquisition, and purchase intention is a crucial step in this process. This study aims to determine 7P marketing mix elements effect on purchase intention in a renovation service company. A quantitative approach was used in this study, involving 144 collected samples who had home renovation plans and lived in Magelang, Yogyakarta, Solo, and the surrounding areas. The data collected were analyzed using SmartPLS4. The results showed that price and promotion significantly influenced purchase intention using home renovation services. Price had the highest impact in influencing purchase intention. While, product, place, people, process, and physical evidence did not significantly influence purchase intention. This study contributes to marketing theory by extending the 7Ps framework to the small-scale construction context, where service tangibility and project-based transactions dominate decision-making. The findings highlight that in the home renovation industry, price and promotion drive purchase intention more strongly than people or process, suggesting the need to adapt traditional marketing mix models for project-based services.